2007
DOI: 10.1063/1.2740641
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on two-photon absorption of dialkylamino substituted distyrylbenzene chromophore

Abstract: Solvent effects on the two-photon absorption of a symmetrical diamino substituted distyrylbenzene chromophore have been studied using the density functional response theory in combination with the polarizable continuum model. It is shown that the dielectric medium has a rather small effect both on the bond length alternation and on the one-photon absorption spectrum, but it affects significantly the two-photon absorption cross section. It is found that both one- and two-photon absorptions are extremely sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 27 publications
4
65
0
1
Order By: Relevance
“…This finding is in agreement with recent theoretical predications of TPA crosssection values of organic chromophores on solvents. [41] Solvents with different polarity may lead to different geometric distortions of a chromophore, thus resulting in a large variation of TPA cross-section values. The TPA cross-section values in toluene (e opt ¼ 2.232, P ¼ 9.9) are found to be the highest for compounds 1FL-4FL, whereas those values in cyclohexane (e opt ¼ 2.028, P ¼ 0.6) are the lowest.…”
Section: Two-photon Absorptionmentioning
confidence: 99%
“…This finding is in agreement with recent theoretical predications of TPA crosssection values of organic chromophores on solvents. [41] Solvents with different polarity may lead to different geometric distortions of a chromophore, thus resulting in a large variation of TPA cross-section values. The TPA cross-section values in toluene (e opt ¼ 2.232, P ¼ 9.9) are found to be the highest for compounds 1FL-4FL, whereas those values in cyclohexane (e opt ¼ 2.028, P ¼ 0.6) are the lowest.…”
Section: Two-photon Absorptionmentioning
confidence: 99%
“…Therefore, to extract the pure 2PA cross section from the Z-scan signal the range of irradiation intensity must be chosen carefully to avoid contribution of other nonlinear processes. Since the measured 2PA cross section depends on many parameters such as the irradiation wavelength, the pulse duration [11,12], the irradiating intensity [13], the specific solvent [14,15] as well as the concentration it is understandable why different authors reported different values for the same compound. To avoid this problem the establishment of a protocol for measuring the 2PA cross sections is of crucial importance [16].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the general observations that the donor-p-acceptor systems show larger TPA activity in moderately polar solvents as compared with that in very high or very low-polarity solvents. [38][39][40] The trend of d…”
Section: View Article Onlinementioning
confidence: 99%